The Effect of Work Discipline, Work Experience and Turnover Intention on Employee Performance at PT. Permodalan Nasional Madani Banjarmasin Branch Office - Joko Suprianto; Adi Susilo Jahja; Saripudin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of this research is to investigate how work discipline, work experience, and turnover intention affect the performance of employees working at PT. Permodalan Nasional Madani Banjarmasin Branch Office. The methodology employed involves the distribution of a questionnaire through online platforms to collect data from a sample of 100 respondents. Structural Equation Modeling (SEM) based on SmartPLS is used to conduct statistical tests. The findings of the study suggest that work discipline and work experience have a positive and significant impact on employee performance, while turnover intention has a negative and significant impact on employee performance